2020
DOI: 10.3389/fnins.2020.583097
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Roles of Ghrelin in Metabolic Syndrome and Secondary Symptoms of Alzheimer’s Disease

Abstract: Although the major causative factors of Alzheimer's disease (AD) are the accumulation of amyloid β and hyperphosphorylated tau, AD can also be caused by metabolic dysfunction. The major clinical symptom of AD is cognitive dysfunction. However, AD is also accompanied by various secondary symptoms such as depression, sleep-wake disturbances, and abnormal eating behaviors. Interestingly, the orexigenic hormone ghrelin has been suggested to have beneficial effects on AD-related metabolic syndrome and secondary sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 168 publications
(217 reference statements)
0
4
0
Order By: Relevance
“…Recent research has highlighted the potential role of ghrelin, a survival and hunger hormone, produced by the stomach, and its receptor, growth hormone secretagogue receptor (GHS-R), in the pathogenesis of AD . Studies have suggested that ghrelin and GHS-R may affect lipid metabolism , and contribute to the development and progression of AD. , To further investigate this potential mechanism, we conducted a study using serum samples from GHS-R knockout 5× FAD (familial Alzheimer’s disease) mice and compared them to normal 5× FAD mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has highlighted the potential role of ghrelin, a survival and hunger hormone, produced by the stomach, and its receptor, growth hormone secretagogue receptor (GHS-R), in the pathogenesis of AD . Studies have suggested that ghrelin and GHS-R may affect lipid metabolism , and contribute to the development and progression of AD. , To further investigate this potential mechanism, we conducted a study using serum samples from GHS-R knockout 5× FAD (familial Alzheimer’s disease) mice and compared them to normal 5× FAD mice.…”
Section: Resultsmentioning
confidence: 99%
“… 61 Studies have suggested that ghrelin and GHS-R may affect lipid metabolism 62 , 63 and contribute to the development and progression of AD. 61 , 64 To further investigate this potential mechanism, we conducted a study using serum samples from GHS-R knockout 5× FAD (familial Alzheimer’s disease) mice and compared them to normal 5× FAD mice.…”
Section: Resultsmentioning
confidence: 99%
“…Edible prebiotics contain dietary fiber that promotes the growth of intestinal flora, which is beneficial to the health of the host. Mice treated with the mixture of probiotics and prebiotics had higher levels of gastrointestinal hormones such as ghrelin, leptin, glucagon-like peptide-1 (GLP1) and insulin-stimulating peptide in plasma, among which ghrelin could counteract the memory impairment and synaptic degeneration of AD [66]. Leptin is a neurotrophic factor that exerts neuroprotective effects against Aβ oligomer-induced toxicity in vitro [67].…”
Section: ) Intervention Of Ad By Transplanting Fecal Flora To Regulat...mentioning
confidence: 99%
“…It is worth noting that initial PNX studies focused on its role in the reproduction system [3,4], however no less important effects were observed, e.g., in memory and anxiety [5,6], as well as in glucose and lipid metabolism [7,8]. Some of these bioactivities exhibit features similar to other neuropeptides like orexins [9], ghrelin [10], or kisspeptin [11]. Moreover, in the hypothalamus, PNX is co-expressed with nesfatin-1 [12].…”
Section: Introductionmentioning
confidence: 99%